Impact of smoking on efflorescence formation on dry-fermented sausages. (April 2019) - Walz, Felix H.; Gibis, Monika; Herrmann, Kurt; Weiss, Jochen
Graphical abstract: Highlights: Magnesium, lactate, and creatine identified as main components of efflorescences. Magnesium suggested to be the main component triggering the crystal formation. Smoking significantly reduced the amount of efflorescences. Low surface pH was responsible for reduction of efflorescences. High mineral concentration prevented mass transport of ionic components. Abstract: The formation of white deposits (efflorescences) on the surface of dry-fermented sausages has been an increasing challenge in the European meat processing industry. As such, the current study investigated the impact of smoking on the formation of efflorescences. We therefore utilized a multistep procedure. Firstly, dry-fermented Salami-type sausages (20 mm caliber) were produced and subsequently exposed to different smoking times (0, 30, 60, and 120 min). Secondly, modified atmosphere was applied to induce efflorescence formation on Salami-type sausages over a storage period of 8 weeks. Thirdly, the surface of the sausages was analyzed by both visual and chemical methods to quantify the amount and major components, which induce the formation of efflorescences. The results revealed that multiple effects simultaneously occurring influenced the efflorescence formation. An increase in smoke exposure significantly decreased the amount of efflorescences on the surface during storage (0 min = 31.6% >30 min = 24.6% >60 min = 7.5% > 120 min = 3.4%) due to a decrease in surface pH. In addition, magnesium, lactate, and creatine were identified as the major components depositing on the surface of the sausages during smoking and storage. Statistical analysis showed high correlation scores between visual and chemical analysis (0.751–0.971), particularly of magnesium indicating its function as a major agent in the formation of efflorescences. Our results might have important implications for the production of processed meat products.